Whole-brain arterial spin labeling perfusion MR imaging in patients with acute stroke - Bokkers, Reinoud P.H. (2012)
BACKGROUND AND PURPOSE: Perfusion MRI can be used to identify patients with acute ischemic stroke that may benefit from reperfusion therapies. The risk of nephrogenic systemic fibrosis, however, limits the use of contrast agents. Our objective was to evaluate the ability of arterial spin labeling (ASL), an alternative non-invasive perfusion technique, to detect perfusion deficits compared with dynamic susceptibility contrast (DSC) perfusion imaging. METHODS: Consecutive patients referred for emergency assessment of suspected acute stroke within a seven-month period were imaged with both ASL and DSC perfusion MRI. Images were interpreted in a random order by two experts blinded to clinical information for image quality, presence of perfusion deficits and diffusion-perfusion mismatches. RESULTS: 156 patients were scanned with a median time of 5.6 (3.0–17.7) hours from last seen normal. Stroke diagnosis was clinically confirmed in 78 patients. ASL and DSC imaging were available in 64 of these patients. A perfusion deficit was detected with DSC in 39 of these patients; ASL detected 32 of these index perfusion deficits, missing 7 lesions. The median volume of the perfusion deficits as determined with DSC was smaller in patients which were evaluated as normal with ASL than in those with a deficit (median, interquartile range; 56 (10–116) vs. 114 (41–225) ml, p=0.01). CONCLUSIONS: ASL can depict large perfusion deficits and perfusion/diffusion mismatches in correspondence with DSC. Our findings show that a fast 2½ minute ASL perfusion scan may be adequate for screening acute stroke patients with contraindications to gadolinium-based contrast agents.